Undiagnosed patent foramen ovale: a rare cause for acute pulmonary embolism and cryptogenic stroke - Fernando, M.S.P.K.; Kumanan, T.; Gerald, S.R. (Sri Lanka College of Internal Medicine, 2025)
Patent foramen ovale (PFO) is a congenital cardiac anomaly found in 25-30% of the population. Though often asymptomatic, it may lead to paradoxical embolism and cryptogenic stroke. We present a case of a young man with simultaneous acute pulmonary embolism (PE), ischaemic stroke, and lower limb deep vein thrombosis (DVT), culminating in cardiopulmonary arrest. Transoesophageal echocardiography revealed an undiagnosed PFO, supporting the theory of a paradoxical shunt causing stroke. This case highlights the critical role of optimising anticoagulation in managing unprovoked DVT. PFO is a silent culprit and may result in adverse outcomes in patients with pulmonary embolism.
Keywords: Acute pulmonary embolism; Cryptogenic stroke; Paradoxical embolism; Patent foramen ovale